Leviticus at Qumran : text and interpretation - Kugler, Robert A. (Vetus Testamentum, Supplements, 2016)
In Leviticus at Qumran: Text and Interpretation Robert A. Kugler and Kyung S. Baek provide an indispensable reference work for understanding how the Book of Leviticus shaped the people of Qumran and their texts. Focusing on issues central to the Qumran community's identity-sacrifice, priesthood, purity, and holiness-Leviticus played a pivotal role in the group's self-understanding. The volume presents all of the texts of Leviticus from Qumran with their variants (with contributions from Eugene Ulrich and Peter Flint), lists over three hundred and fifty uses of Leviticus in the scrolls from Qumran, and provides brief summaries of each of those uses. It provides all the data necessary to explore how Leviticus shaped the people of the scrolls.